THE INFLUENCE OF HUMAN RESOURCES ON THE DEVELOPMENT OF LEADING TOURISM DESTINATIONS IN SERBIA - Kordić, Nikolina; Milićević, Snežana (The European Journal of Applied Economics, 2020)
The objective of this paper is to show the correlation between the volume and dynamics of tourist traffic and accommodation capacity and the scope and dynamics of employment in the hotel industry of Serbia. The most developed destinations of Serbia (in the field of city tourism Belgrade and Novi Sad, spa tourism - Vrnjačka Banja and Sokobanja and mountain tourism - Zlatibor and Kopaonik) were chosen to be the subject of research. The first part of the paper discusses the connection between the study of tourist destinations, on the one hand, and human resources, on the other hand. In the second part of the paper, corresponding conclusions are drawn regarding the influrnce of human resources on the development of the leading tourist destinations in Serbia by using systematization and presentation of statistical data, by analyzing the quantification of the effect of employment on tourist traffic, based on correlation and regression analysis, using the analytic-synthetic and comparative methods.